2012
DOI: 10.1186/1472-6963-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of neonatal hearing screening program in china: should universal screening be prioritized?

Abstract: BackgroundNeonatal hearing screening (NHS) has been routinely offered as a vital component of early childhood care in developed countries, whereas such a screening program is still at the pilot or preliminary stage as regards its nationwide implementation in developing countries. To provide significant evidence for health policy making in China, this study aims to determine the cost-effectiveness of NHS program implementation in case of eight provinces of China.MethodsA cost-effectiveness model was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The term "permanent congenital and early-onset hearing loss", or simply "hearing loss", is used more broadly to capture all degrees of hearing loss based on hearing threshold in the better ear averaged over frequencies 0.5, 1, 2, and 4 kHz, classified as: mild (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), moderate (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), moderately severe (50-64 dBHL), severe (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79), and profound (80)(81)(82)(83)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "permanent congenital and early-onset hearing loss", or simply "hearing loss", is used more broadly to capture all degrees of hearing loss based on hearing threshold in the better ear averaged over frequencies 0.5, 1, 2, and 4 kHz, classified as: mild (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), moderate (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), moderately severe (50-64 dBHL), severe (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79), and profound (80)(81)(82)(83)…”
Section: Introductionmentioning
confidence: 99%
“…33 This is corroborated by more recent studies on the cost-effectiveness of NHS in the People's Republic of China, which also has vast underdeveloped communities. 34,35 WHO experts further reiterate that regardless of the approach adopted, the EHDI program should be linked to existing health care, social, and educational systems, and that the procedures and outcomes of the program be documented for effective follow-up. 33 Additionally, the need to ensure that targeted/selective hearing screening (THS) was based on context-specific risk factors, ideally guided by findings from well conducted pilot UHS programs and other local epidemiological data, is emphasized.…”
mentioning
confidence: 99%
“…Newborn screening combined with a Phe-restricted therapeutic diet throughout childhood can help to control the progress of PKU for most patients (11). Research shows that with a higher newborn screening rate, earlier treatment can be received by patients, and the prognosis will be better (12)(13)(14). Therefore, an effective newborn screening for PKU is indeed needed.…”
Section: Newborn Screening For Pkumentioning
confidence: 99%
“…However, PKU is a treat-able and prevent-able disease (9,10). A screening program, especially early detection, combined with a Phe-restricted therapeutic diet can help to control the development of PKU for most patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Newborn screening combined with a Phe-restricted therapeutic diet throughout childhood can help to control PKU in most patients (5). Studies have shown that a higher rate of newborn screening and earlier treatment can lead to a better prognosis for patients (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%